2017
DOI: 10.1017/s1092852917000128
|View full text |Cite
|
Sign up to set email alerts
|

A biopsychosocial evaluation of the risk for suicide in schizophrenia

Abstract: The risk of suicide is greatly increased in individuals with schizophrenia. Previous research has identified several potential risk factors for suicidal behavior in schizophrenia, although their ability to independently predict suicide is limited. The objective of this review was to systematically analyze and identify the interaction between the proposed risk factors in the literature that may predict suicidal behavior in schizophrenia. Articles that explored suicidal behavior and suicide risk in schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Comorbid depression and a history of suicidal behavior are important contributors to suicide risk in patients with schizophrenia [33,53,56]. One study showed that depressive symptoms, suicidal ideation and plans and a history of suicide attempts are amongst the most important forecasters of suicidal behavior in the early phases of schizophrenia [57].…”
Section: Risk Factors Related To Comorbid Disordersmentioning
confidence: 99%
“…Comorbid depression and a history of suicidal behavior are important contributors to suicide risk in patients with schizophrenia [33,53,56]. One study showed that depressive symptoms, suicidal ideation and plans and a history of suicide attempts are amongst the most important forecasters of suicidal behavior in the early phases of schizophrenia [57].…”
Section: Risk Factors Related To Comorbid Disordersmentioning
confidence: 99%
“…In schizophrenic patients, the risk of suicide is higher (Hettige et al 2018 ; Kasckow et al 2011 ), suicide deaths being common (Tousignant et al 2011 ). Thus, suicide is an important cause of death among patients with schizophrenia (Gómez-Durán et al 2012 ; Togay and Lippmann 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotics are useful in the treatment of schizophrenia but not in catatonia and it may also worsen the case by inducing neuroleptic malignant syndrome. Benzodiazepines are effective in the treatment of both malignant catatonia and neuroleptic malignant syndrome [8].…”
Section: Discussionmentioning
confidence: 99%